2005
DOI: 10.1590/s0100-879x2005000400019
|View full text |Cite
|
Sign up to set email alerts
|

Heart rate variability in athletes and nonathletes at rest and during head-up tilt

Abstract: The purpose of the present study was to determine if autonomic heart rate modulation, indicated by heart rate variability (HRV), differs during supine rest and head-up tilt (HUT) when sedentary and endurance-trained cyclists are compared. Eleven sedentary young men (S) and 10 trained cyclists (C) were studied. The volunteers were submitted to a dynamic ECG Holter to calculate HRV at rest and during a 70º HUT. The major aerobic capacity of athletes was expressed by higher values of V. O 2 at anaerobic threshold… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
45
1
8

Year Published

2008
2008
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 71 publications
(62 citation statements)
references
References 34 publications
4
45
1
8
Order By: Relevance
“…During HUT, the mean heart rate was 86 beats min -1 with HF and LF components of 28.6 NU and 63.4 NU respectively J Physiol Sci (2009) 59: 31-36 33 ventilation, as shown by others [23][24][25][26][27]. Also, in the current study, a decrease in HF cardiac variability was shown with HUT, again similar to the findings of others [14,[18][19][20]33]. However, in the present study, when using the HF component as an index of cardiac vagal tone, the expected vagal withdrawal during HUT was reduced when the HF component was already elevated by an increase in ventilation.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…During HUT, the mean heart rate was 86 beats min -1 with HF and LF components of 28.6 NU and 63.4 NU respectively J Physiol Sci (2009) 59: 31-36 33 ventilation, as shown by others [23][24][25][26][27]. Also, in the current study, a decrease in HF cardiac variability was shown with HUT, again similar to the findings of others [14,[18][19][20]33]. However, in the present study, when using the HF component as an index of cardiac vagal tone, the expected vagal withdrawal during HUT was reduced when the HF component was already elevated by an increase in ventilation.…”
Section: Discussionsupporting
confidence: 91%
“…Pagani et al [5] observed significant increases in cardiac variability at low frequencies with HUT, but also reported no correlation between the increases in the LF component and the tilt-induced increase in heart rate. Similarly, higher LF NU during HUT was recorded in trained and untrained subjects [33] but no correlation between time and frequency domain measures were reported. In the current study, the lack of a clear directional change in the LF component of HRV may reflect the small number of subject tested.…”
Section: Discussionmentioning
confidence: 94%
“…4,8,[10][11][12][13]15,17,18,[19][20][21]25,27,[30][31][32][34][35][36]38,39,45,47 The results of 10 articles on ANS response measured during exercise are shown in Table I. Some authors expressed concern about the measurement of spectral analysis of HRV during exercise, while others reported increases (↑), decreases (↓) and no changes in variability indicators (↔) of sympathetic (SNS) and parasympathetic (PNS) influence.…”
Section: Resultsmentioning
confidence: 99%
“…The result of the logistic regression model supported the hypothesis that CDR index adequately represents the parasympathetic control of the heart rate, and thus it could be applicable to estimate the positive adaptation to cardiorespiratory fitness (Buchheit et al, 2010;Bucheit & Ginder, 2006;De Meersman, 1996;Martinelli et al, 2005;Moreira et al, 2013;Plews et al, 2013;Yataco, Fleisher, & Katzel, 1997), or the autonomic control of post-exercise heart rate (Martinelli et al, 2005;Moreira et al, 2013;Plews et al, 2013) and the increasing vagal activity (Trevizani, Belchimol-Barbosa, & Nadal, 2012). Therefore, it is possible to speculate that regular aerobic exercise, with enough intensity to cause further increase in VO2max could be evaluated by the CDR index.…”
Section: Heart Rate Variability and Aerobic Fitness| 55mentioning
confidence: 60%